Patristic literature in Arabic translations - Roggema, Barbara; Treiger, Alexander (Arabic Christianity, 2020)
"Patristic Literature in Arabic Translations offers a panoramic survey of the Arabic translations of the Church Fathers, focusing on those produced in the Palestinian monasteries and at Sinai in the 8th-10th centuries and in Antioch during Byzantine rule (969-1084). These Arabic translations frequently preserve material lost in the original languages (mainly Greek and Syriac). They offer crucial information about the diffusion and influence of patristic heritage among Middle Eastern Christians from the 8th century to the present. A systematic examination of Arabic patristic translations paves the way to an assessment of their impact on Muslim and Jewish theological thought".